1994
DOI: 10.1042/bst0220931
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the role of glutathione reductase using transgenic plants

Abstract: The types of environmental stresses, both natural and anthropomorphic in origin, and physiological stresses that a plant is subjected to throughout its life are manifold. Examples are low temperatures combined with high light intensities, drought conditions, damage caused by pathogens, air-and waterborne pollutants and premature senescence [ 1,2].The physiological basis of the damage suffered by a plant during stress can often be explained as perturbations in oxygen metabolism leading to enhanced production of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…This result is similar to the results obtained from transformation of GR localized in the cytosol (Foyer et al ) and is in contrast to the results obtained from the transformation of GR localized in the chloroplast in higher plants, i.e. that the glutathione pool size can be increased (Foyer et al , , Mullineaux et al ). Additionally, GR of bacterial origin can function in the chloroplasts of plant cells to increase both the GSH/GSSG ratio and the total glutathione pool (Noctor et al ).…”
Section: Discussionsupporting
confidence: 89%
“…This result is similar to the results obtained from transformation of GR localized in the cytosol (Foyer et al ) and is in contrast to the results obtained from the transformation of GR localized in the chloroplast in higher plants, i.e. that the glutathione pool size can be increased (Foyer et al , , Mullineaux et al ). Additionally, GR of bacterial origin can function in the chloroplasts of plant cells to increase both the GSH/GSSG ratio and the total glutathione pool (Noctor et al ).…”
Section: Discussionsupporting
confidence: 89%
“…Finally, GSH participates in many diverse cellular reactions; augmented levels may exert more indirect effects on protein synthesis and gene expression, which would contribute both to the observed decrease in susceptibility to photoinhibitory treatment and to the enhanced rates of recovery upon remova1 of the treatment. These results suggest that the high-chloroplastic-GR expressors are more robust as a result of the introduction of bacterial GR into the chloroplast, a conclusion in line with observations on other species transformed to express GR in the chloroplast (Aono et al, 1991(Aono et al, , 1993Mullineaux et al, 1994). This may prove to be of major ecological and practical significance and may have implications for improving methods of tree establishment.…”
Section: Dlscusslonsupporting
confidence: 75%
“…This system may provide a means of studying the mechanisms that determine the level of GR activity in two discrete intracellular compartments. Recent work with N. tabacum (var Samsun) transformed with the GR cDNA from Pisum sativum (Creissen et al, 1991) has shown that overexpression of GR in the chloroplast, but not the cytosol, led to increases in the foliar GSH level by up to 50% (Mullineaux et al, 1994). In the present study, the foliar GSH level was also increased as a result of overexpression of bacterial GR in the chloroplast.…”
Section: Dlscusslonsupporting
confidence: 65%
“…The high-GSH pool maintained by GR in cells is necessary for active protein function and avoids unspecific formation of mixed disulfide bonds that cause protein inactivation or aggregation (Foyer and Noctor 2005b). Over-expression of the E. coli GR in chloroplast increased both total glutathione contents and GSH : GSSG ratio (Mullineaux et al 1994;Foyer et al 1995). GPX is the principle cellular enzyme capable of membrane lipid peroxidation repair and is generally considered to be the main line of enzymatic defense against oxidative membrane damage (Ursini et al 1995;Kühn and Borchert 2002).…”
Section: Discussionmentioning
confidence: 99%